Puente para cuidar (bridge to caring): A palliative care patient navigator and counseling intervention to improve distress in Latino/as with advanced cancer. Issue 4 (27th December 2019) - Bekelman, David B.; Fink, Regina M.; Sannes, Timothy; Kline, Danielle M.; Borrayo, Evelinn A.; Turvey, Carolyn; Fischer, Stacy M.
Abstract: Objective: Interventions are needed to improve mental health (ie, depression, anxiety) and palliative care (ie, symptoms, goals of care, and advance care planning) outcomes in Latino/as with advanced cancer. Methods: An interprofessional study team used the ecological validity model and a participatory approach to adapt an evidence‐based counseling intervention for Latino/as and integrate the counseling intervention with an evidence‐based patient navigator intervention. Next, a small pilot study was conducted to understand and improve the feasibility of the integrated puente para cuidar intervention. Results: Adaptations were made to language, literacy, and content of the counseling intervention, and video vignettes of the counseling case studies were produced on the recommendation of Latino/a stakeholders. Bicultural, bilingual patient navigators were used as "cultural brokers" between Latino/a patients and the counselor. The pilot study of puente para cuidar demonstrated feasibility based on participant perception of helpfulness and acceptability and nearing goal visit completion rates. Conclusions: A culturally adapted intervention to address mental health and palliative care needs in Latino/as with advanced cancer was developed from prior evidenced‐based interventions using a cultural adaptation model and a participatory approach. The intervention is ready for effectiveness testing.